2011
DOI: 10.1055/s-0031-1272552
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association between Cardiac Troponin-I and Soluble Receptor for Advanced Glycation End Products in Patients with Non-ST-Segment Elevation Myocardial Infarction

Abstract: Interaction of advanced glycation end products (AGEs) with the receptor for advanced AGEs (RAGE) results in activation of nuclear factor kappa-B, release of cytokines, expression of adhesion molecules, and induction of oxidative stress. Oxygen radicals are involved in plaque rupture contributing to thromboembolism, resulting in acute coronary syndrome (ACS). Thromboembolism and the direct effect of oxygen radicals on myocardial cells cause cardiac damage that results in the release of cardiac troponin-I (cTnI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…However, low sRAGE concentrations are reported to occur in various conditions during the acute clinical phase in addition to changes reported in DKA. These conditions include: 1) atrial fibrillation (33); 2) low sRAGE and high cardiac troponin in non-ST segment elevation myocardial infarction (34); and 3) the autoimmune condition of multiple sclerosis (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, low sRAGE concentrations are reported to occur in various conditions during the acute clinical phase in addition to changes reported in DKA. These conditions include: 1) atrial fibrillation (33); 2) low sRAGE and high cardiac troponin in non-ST segment elevation myocardial infarction (34); and 3) the autoimmune condition of multiple sclerosis (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with non-ST elevation myocardial infarction did not have elevated sRAGE due to the weaker inflammatory response. McNair et al [11, 22] found that plasma sRAGE levels were decreased in patients with non-ST-segment elevation myocardial infarction, while the levels of TNF- α and hypersensitive C-reactive protein increased. Whether in the control group or the infarction group, the level of sRAGE was negatively correlated with TNF- α and high-sensitivity C-reactive protein.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE, a multiligand receptor, interacts with a variety of ligands including the AGEs, S100 calcium-binding protein family, high-mobility group box 1 (HMGB1), beta amyloid-like peptides, and β 2 integrins [2, 5, 7]. The binding of RAGE with its ligands results in amplifying the inflammatory response and tissue injury via the activation of nuclear factor kappa-B, the release of cytokines, the expression of adhesion molecules, and the generation of reactive oxygen species, contributing to the pathogenesis of atherosclerosis and plaque rupture [811].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were collected before the revascularization. Similarly, McNair et al found lower levels of sRAGE in patients with non-STEMI compared to the controls, and time of blood sample collection was not indicated [ 51 54 ].…”
Section: Srage In Patients With Acute Coronary Syndrome (Acs)mentioning
confidence: 99%